The Power of Customer Relationship Management – A New Marketing Trend for Hospitality in Globalization Context (Asian Journal of Social Science Studies, 2021)
Customer Relationship Management is known as an effective method which helps administrations to solve many customers problems. Nowadays, every business which wants to survive and develop needs to improve its customer relationship management department. This research analyses the literature review of Hospitality, Customer Relationship Management (CRM), summarizes methodology to proceed and evaluates the reality of CRM for hospitality in Hanoi Old Quarter in Vietnam. Based on researching data result, author takes solutions to improve CRM for hospitality in Hanoi Old Quarter in Vietnam. In the hospitality sector, especially for hotel business in the old city center of Hanoi, 90% of visitors are foreigners and mainly through online (OTA) sources. The booking process for foreign visitors traveling to Hanoi was presented in the study of Dr. Ha Nguyen Van (2015) "The power of online marketing for hospitality in Vietnam in globalization context" showed that before booking a room, they were able to find out the hotel by reading reviews of customers who had experienced the hotel through the channels such as tripadvisor, booking.com .... The Old Quarter hotel is primarily concerned with customer reviews, customer service to keep customers happy and satisfy about the hotel. And these good reviews are the most effective way to help hotels boost sales, boost hotel branding, and promote the image of the hotel. This research has a scope of surveys which were done in Hanoi, Vietnam. Nevertheless, it serves as the grounds for all travel agencies and hotels doing business in Hanoi to re-examine their online marketing activities and consider the findings of this paper as reference for further research.